Assessing knowledge, attitude, practice towards type II diabetes mellitus and their blood glucose level among public in selected areas of Bachok District, Kelantan - Rosmini Remali,; Asma Ali,; Noor Salihah Zakaria,; Hayati Mohd Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Diabetes is a major health problem in Malaysia particularly in Kelantan state. This cross-sectional study was designed to determine the knowledge, attitude and perceive practice towards type II diabetes among the public residants of Kelantan in relation towards their blood glucose level. About 68 respondents aged from 18 to 59 years old, were approached personally to participate in this study. Data collection was done through face-to-face interview using a questionnaire consisted of four sections; knowledge, attitude, and perceive practice (KAP) questionnaire including recent fasting blood glucose (FBG) readings. The results showed that most of the respondents had a moderate level of knowledge (54.4%, n=37), positive attitude (72%, n=49), and good perceive practice level (51.5%, n=35) towards diabetes mellitus. There was no significant relationship between knowledge, attitude, and perceive practice level towards diabetes mellitus at p<0.05. KAP level towards diabetes mellitus showed no significant relationship with blood glucose level at p<0.05. Findings indicate that most respondents had normal BMI (18.5 – 24.9) (64.7%, n=44) and normal FBG reading (< 6.1 mmol/L) (92.6%, n=63). As conclusion, respondents with higher educational level were more likely to have a higher level of knowledge about diabetes mellitus; however, this did not influence attitude, perceive practice and fasting blood glucose of respondents.